2006
DOI: 10.1007/s11094-006-0194-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and medicobiological properties of chaga (review)

Abstract: Data on the chemical composition and pharmacological activity of chaga (Inonotus obliquus) are reviewed. The possible mechanisms of action and factors responsible for the discrepancy of data available in the literature are discussed. The physical and chemical characteristics of melanin (polyphenolic chromogenic humin-like complex present in chaga) and its role in the regulation of physiological processes are considered.The curative properties of chaga have been known from ancient times. Despite many ages of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 6 publications
2
61
0
2
Order By: Relevance
“…Thus, polyphenols, triterpenoids, and polysaccharides in the birch were considered as simulators for the steroid biosynthesis of I. obliquus. Fungi digest food outside their bodies by releasing enzymes into the surrounding environment, breaking down organic matter into a form the fungus can then absorb (17,20,24,25). These compounds such as saccharides, terpenoids, and phenols not only involved in sterol biosynthesis directly, but also glucose derived from polysaccharides metabolism was beneficial for sterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, polyphenols, triterpenoids, and polysaccharides in the birch were considered as simulators for the steroid biosynthesis of I. obliquus. Fungi digest food outside their bodies by releasing enzymes into the surrounding environment, breaking down organic matter into a form the fungus can then absorb (17,20,24,25). These compounds such as saccharides, terpenoids, and phenols not only involved in sterol biosynthesis directly, but also glucose derived from polysaccharides metabolism was beneficial for sterol biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Pilat (Hymenochaetaceae), commonly known as Chaga, has been used as a folk remedy in Russia and Eastern Europe since the 16th century for a wide variety of human diseases without any intolerable toxic side effects (Shashkina et al, 2006;Wasser and Weis, 1999). Chaga tinctures were among the most popular preparations in the North and Middle Russia, which were used as remedies for the prophylaxis and treatment of gastric disorders and even cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has been reported that the aqueous extract of Inonotus obliquus significantly inhibited the growth of Sarcoma 180 cells (Chen et al, 2007) and HepG2 cells (Youn et al, 2008). However, though Inonotus obliquus mushrooms are increasingly being used to treat a various cancer, it is relatively little knowledge of their mechanism of action (Shashkina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%